2011
DOI: 10.1124/dmd.111.041848
|View full text |Cite
|
Sign up to set email alerts
|

Phenacetin Pharmacokinetics in CYP1A2-Deficient Beagle Dogs

Abstract: ABSTRACT:Phenacetin is widely used as an in vitro probe to measure CYP1A2 activity across species. To investigate whether phenacetin can be used as an in vivo probe substrate to phenotype CYP1A2 activity in dogs, beagle dogs previously genotyped for a single nucleotide polymorphism that yields an inactive CYP1A2 protein were selected and placed into one of three groups: CC (wild-type), CT (heterozygous), or TT (homozygous mutants). The dogs were dosed with phenacetin orally at 5 and 15 mg/kg and intravenously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The CYP1A2 enzyme is known to be expressed in all mammalian livers, with few species differences in function or regulation and high amino acid sequence homology (Parkinson and Ogilvie, 2008). Phenacetin is a substrate widely used as an in vitro and in vivo probe (except for in beagle dogs; Whiterock et al, 2012) to measure CYP1A2 activity because the metabolism of phenacetin to acetaminophen is thought to be a selective CYP1A2-mediated reaction (Distlerath et al, 1985;Tassaneeyakul et al, 1993). Hence, in the present study, the inhibitory effects of PRN and IPRN on CYP1A2-mediated metabolism were assessed in vitro and in vivo in rats and in vitro in humans using phenacetin as the probe substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP1A2 enzyme is known to be expressed in all mammalian livers, with few species differences in function or regulation and high amino acid sequence homology (Parkinson and Ogilvie, 2008). Phenacetin is a substrate widely used as an in vitro and in vivo probe (except for in beagle dogs; Whiterock et al, 2012) to measure CYP1A2 activity because the metabolism of phenacetin to acetaminophen is thought to be a selective CYP1A2-mediated reaction (Distlerath et al, 1985;Tassaneeyakul et al, 1993). Hence, in the present study, the inhibitory effects of PRN and IPRN on CYP1A2-mediated metabolism were assessed in vitro and in vivo in rats and in vitro in humans using phenacetin as the probe substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, other (human selective) CYP1A2 substrates including caffeine and melatonin were unaffected by the deficiency, implying that dog CYP1A2 does not selectively metabolize these latter drugs (unlike human CYP1A2). A recent study of phenacetin pharmacokinetics following oral and intravenous administration to CYP1A2 genotype Beagles 15 showed about 2-fold higher phenacetin exposure (based on area under the plasma concentration time curve; AUC) after oral administration in CYP1A2 deficient dogs, but there were much smaller (non-significant) differences in phenacetin levels after intravenous exposure. The authors concluded that phenacetin was not a selective or robust in vivo probe for CYP1A2 probably because of metabolism of phenacetin by other enzymes (such as canine CYP1A1 and/or canine CYP2A13).…”
Section: Canine Cyps With Known Genetic Polymorphismmentioning
confidence: 99%
“…The following provides an update on research studies that have been newly identified since those reviews were published. No enzyme protein or activity Mise, Hashizume, and Komur (2008), Mise et al (2004), Tenmizu, Endo, Noguchi, and Kamimura (2004), Kamimura (2006); , Tenmizu, Noguchi, Kamimura, Ohtani, and Sawada (2006) About twofold increase in phenacetin plasma concentrations Whiterock, Morgan, Lentz, Orcutt, and Sinz (2012) Up to 17-fold increase in plasma concentrations of a test compound in homozygous deficient dogs , Tenmizu, Noguchi, Kamimura, Ohtani, et al (2006) Highest allele frequencies in Irish Wolfhounds 2000; Sams, Muir, Detra, & Robinson, 1985;Zoran, Riedesel, & Dyer, 1993). Two CYP2B11 polymorphisms were reported as part of a doctoral thesis (Wenker, 2009).…”
Section: Drug Me Tabolis M P Olymorphis Ms In Dog S and C Atsmentioning
confidence: 99%